Note Respecting the Book-Stamp of Archbishop Hamilton of St Andrews, 1548-1571 (Proceedings of the Society of Antiquaries of Scotland, 1864)
This is a note to explain the significance and rarity of book-stamps. He notes that at the time of writing there was only one original book-stamp in the Society’s collection and suggests that this might be an interesting area of study in future.